Pengaruh Sosial Budaya Ibu Menyusui Terhadap Perkembangan Motorik Kasar 7-12 Bulan di Wilayah Kerja Puskesmas Malimongan Baru (Window of Public Health Journal, 2025)
Fulfillment of health is strongly supported by various aspects, one of which is the socio-cultural aspect. This study aimed to determine the socio-cultural influence of breastfeeding mothers on gross motor development in infants aged 7-12 months in the Malimongan Baru Health Center work area in 2022. The research, an analytical survey with a cross-sectional study approach, used a total sampling technique with a total of 109 samples. The sampling technique was by accidental sampling. The gross motor development of infants was measured using the DDST questionnaire, a widely accepted tool in child development research. Data analysis was conducted using the chi-square test, a statistical method commonly used in health research. The results showed that there was no socio-cultural influence on gross motor development in infants aged 7-12 months. There is no relationship between maternal breastfeeding history and gross motor development, with α (0.05) obtained a p value = 0.0518 α(0.05).